A randomised clinical trial comparing interferon-α and intravenous immunoglobulin in polyneuropathy associated with monoclonal IgM. Issue 1 (1st July 1997) - Mariette, Xavier; Chastang, Claude; Louboutin, Jean-Pierre; Leger, Jean-Marc; Clavelou, Pierre; Brouet, Jean-Claude
Abstract : OBJECTIVES: The polyneuropathy associated with a monoclonal IgM directed to the myelin associated glycoprotein (MAG) is a specific entity with a putative causal link between the IgM and the neuropathy. The small benefit offered by alkylating agents or plasma exchanges in these patients justifies the search for alternative treatments. METHODS: A 12 month multicentre, prospective, randomised, open clinical trial was carried out comparing intravenous immunoglobulin (IVIg; 2g/kg and then 1 g/kg every three weeks) and recombinant interferon-α (IFN-α; 3 MU/m 2 subcutaneously three times weekly). The main end point was a clinical neuropathy disability score (CNDS) after six months of treatment. Twenty patients were enrolled; 10 were assigned to IVIg and 10 to IFN-α. RESULTS: At six months, one out of 10 patients treated with IVIg had a CNDS improvement of more than 20% whereas eight out of 10 patients treated with IFN-α had such an improvement (P=0.005). The mean CNDS worsened by 2.3 (SD 7.6) (8%) in the IVIg group whereas it improved by 7.5 (SD 11.1) (31%) in the IFN-α group (P=0.02). This improvement persisted after 12 months and was mainly related to an improvement of the sensory component (P=0.02) whereas the motor component was unchanged (P=0.39). Electrophysiological data did not show improvement of motor nerve conduction velocities whereas sensory nerve conduction velocities improved in the upper limbs. A decrease in the level of the monoclonal IgM was seen in two patients treated with IFN-α. At the end of the treatment, antibody activity to MAG was still detected in the serum of all patients. CONCLUSION: IVIg, as used in this study, did not improve patients with polyneuropathy and monoclonal IgM. By contrast, although its mechanism of action remains to be fully elucided, IFN-α was effective in eight out of 10 patients at six months.